Modeling anomalous diffusion from statistics to mathematics - Deng, Weihua; Xu, Pengbo; Hou, Ru 1990-; Wang, Wanli 1987- (World Scientific, 2020)
One of the authors, Weihua Deng, has an interdisciplinary research background with a deep understanding on the related anomalous models from the viewpoint of mathematics and physics In this book, we not only introduce the widely investigated models but also discuss some new topics, for example, infinite densities, functionals, etc. This book will get more attention from undergraduates and some high-level students"--